Wrocław in comparison with other European creative cities - Dec, Beata; Greg, Richards (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Cities and metropolises are progressively adopting the concept of the ‘creative city’, in an attempt to differentiate themselves from other cities, and as a remedy for problems of urban development in the postindustrial economy. The creative city combines traditional cultural products, cultural services and heritage with the emerging creative industries such as media, entertainment or architecture. This paper examines how the creative city concept is being developed in Central Europe, analysing Wrocław as an example of the Polish creative city, compared with Budapest, as a Creative City of Design and Prague, as a Creative City of Literature
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 473, s. 137-147
Keywords: creative cities; economic growth; Wrocław; Budapest; Prague; miasta kreatywne; wzrost gospodarczy; Budapeszt; Praga